Zimdancehall: a rising platform in addressing socio-political injustices through lyrics. - Goremusandu, Tapiwa (Midlands State University, 2017)
Present day Zimbabwe though being deemed by the government as a free country embedding the concept of freedom of speech it is still plagued with massive music censorship amongst the predominant genres. Since the late 1800s music has been a major influencing player in indoctrinating people. Music is an essential tool use in public discourse to promote, affirm and subvert political hegemonies. Musicians play a pivotal role in society of exposing the injustices perpetuated by governments and those in power. This research explores the role played by Zimdancehall music in the conscientisation of society about political injustices and questioning of government actions that harm citizens. An investigation of the recent rising trend of the Zimdancehall music genre speaking out on the socio-political injustices occurring in Zimbabwe is the basis of this research. A thorough analysis of the lyrics and literary devices, is used to identify the mention of socio-political chaos in Zimbabwe and its effect.